Towards a formalist theological poetics : practising what you preach in the prose writings of Thomas Merton - Seal, P (2015)
The argument of the thesis is that the literary forms of Thomas Merton’s prose writings embody theological claims he makes elsewhere at the level of content. Specifically, the five chapters of the thesis show that Merton not only writes about the themes of self-denial, simplification, observing the ‘thereness’ of the world, and (in two distinct ways) apprehending God in darkness and obscurity, but that he also enacts those themes in the way he writes prose. The thesis offers an original and significant contribution to three main fields of enquiry. Firstly, when analysing Merton’s prose I employ methods espoused by New Formalist literary critics, but I apply their reading strategies to the theological dimensions of literary form. Secondly, my work builds upon claims made by theologians of form about the link between literary genres or forms and issues surrounding, for instance, the character of God, but it does so in a novel way, by employing New Formalist close reading strategies. Thirdly, the thesis offers a new method of enquiry for Thomas Merton Studies, by performing the first extended literary-critical account of his prose. In sum, the thesis opens up new theoretical territory for Formalism, new specific material for the theology of form, and a new methodology for Merton Studies. Besides the introductory and concluding chapters, all of the chapters of the thesis are structured in the same way. Each includes an expositional section in which I quote from Merton’s thoughts on, for example, self-denial, and a literary-critical section, in which I read the forms of Merton’s prose in terms of the content-claims already outlined. The goal of this methodology is, at every stage, to show that Merton enacts his own theologically-rooted content claims in the forms of his prose.